The Current State оf Spells аnd Incantations Among the Khorchin Mongols (With Examples Related to Birds and Sky-Pleasing Rituals) - Wang , Saruul; Dorjpalam, Mandakh (Mongolian Journal of Arts and Culture, 2025)
This study investigates the current state of spell (dom) usage related to rituals for warding off evil, invoking blessings, and communicating with the heavens among the Khorchin Mongols. A survey involving 354 people from Tongliao city and surrounding rural areas revealed that respondents generally possess limited understanding of spell culture. Some forms and variations of spells were confused, unknown, or remained hidden. An ethnographic field survey using the “dialogic method” was conducted, particularly focusing on young respondents aged 15-34. The questionnaire showed that a majority of younger respondents expressed negative attitudes, such as “never use spells,” “completely unaware,” or “superstitious.” Although they verbally affirmed the importance of preserving Mongolian culture, about 63.47% explicitly stated their ignorance regarding the meaning and use of these spells, indicating a significant rupture in cultural continuity among younger generations. However, interviews with villagers aged 50 and above including herders, farmers, traditional healers, and artisans showed that they still vividly recall ritual actions and applications associated with spells, including curses (haraal dom) and incantations for warding off evil (shivshleg). This suggests that spell culture remains alive as a fundamental component of the Mongolian cultural heritage. Furthermore, rediscovering, documenting, and preserving gradually forgotten spells constitute a central value of this research. Additionally, comparative analysis revealed both similarities and distinct differences between the spell culture of cross border Mongols and that of the Khorchin region in eastern Inner Mongolia, laying valuable groundwork for future comparative research. Therefore, studying the spell culture of cross border Mongolian communities should be viewed as crucial for cultural inheritance among younger generations, significantly contributing to preserving and revitalizing collective cultural memory. Хорчин монголчуудын дом шившлэгийн хэрэглээний өнөөгийн байдал (Жигүүртэн болон тэнгэр аргадахуйд холбогдох домын жишээнд) Хураангуй: Хорчин монголчуудын дунд жигүүртэн болон тэнгэр аргадахуйд холбогдох домын хэрэглээний өнөөгийн байдалд тандалт судалгаа хийж үзэв. Тунляо хотын болон орон нутгийн 354 хүнээс судалгаа авч боловсруулалт хийхэд домын соёлын талаар тун тааруу ойлголттой байх бөгөөд домын зарим төрөл, хувилбарууд мартагдсан, огт мэдэхгүй, мөн далд нууцлаг байдалтай байгаа нь ажиглагдлаа. Судалгаанд этнопоэтик онолын “диалогийн арга”-ыг ашиглаж, 15-34 насны залуучуудын дунд анкетын аргаар явуулсан судалгаанд “дом хэрэглэдэггүй”, “огт мэдэхгүй”, “мухар сүсэг” гэсэн хэдий ч “монгол соёлоо өвлүүлэх” хэрэгтэй гэж 63,47% нь хариулсан нь домын соёл мартагдаж байна гэсэн дүгнэлтэд хүргэсэн билээ. Энэхүү судалгааны үр дүнд орон нутагт амьдарч буй малчин, тариачин, сэхээтэн 50-аас дээш насныхантай хөөрөлдөхөд домын зан үйл ил үйлдэгддэггүй ч шившлэг зэргийг хараахан мартаагүй байгаа нь чухал үнэ цэнтэй болох нь тогтоогдож байгаа юм. Харин мартагдсан домуудыг сэргээн сануулж, бичиж тэмдэглэн авсан нь бидний судалгааны нэгэн зорилт биелж байгаа төдийгүй, хил дамнасан монгол угсаатны соёлын өвөрмөц байдлыг монголын адил төстэй домуудтай харьцуулан үзсэн нь дараа дараагийн судалгааны эх хэрэглэгдэхүүн болохуйц ач холбогдолтой болсон. Ийнхүү хил дамнасан монгол үндэстний соёлын түүхийг залуу хойч үеийнхэндээ үлдээж буй нь чухал ач холбогдолтой хийгээд соёлын хүн судлалд хамаарах, нийгэм-соёлын нэгэн орон зайн хүрээн дэх (Хорчин нутагт дахь) домын соёлыг хадгалж, хамгаалах, өвлүүлэн үлдээхэд бага боловч хувь нэмэр оруулж байгаа болно. Түлхүүр үгс: жигүүртэн шувуу, шаазгай, элээ, шар шувуу, хуй салхи, хур бороо андгай, бөө